Nonlinear equation of quark-gluon cascade - Temiraliev, A.T.; Lebedev, I.A.; Danlybaeva, A.K. (Хабаршы. Физика сериясы, 2018)
On the basis of experimental data on the structural functions of hadrons using the method of Poincare sections we introduce the nonlinear equation of quark-gluon cascade via recurrence relation taking into account merge processes of quarks and gluons. Introduced a discrete map is based on the hypothesis of self-similarity of the evolution of the quark-gluon structure of hadron and the evolution operator are the distribution of quarks and gluons. It is speculated that stochastic quantum fluctuations in strongly correlated quark-gluon system describes the so-called deterministic chaotic dynamics. Carried out fractal analysis of emerging structures (attractors), which stability is determined by Lyapunov exponents. The formation of stable structures in nonlinear quark-gluon evolution, apparently, is connected with the mechanism of hadronization.